If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5c + -4)(c + 6) = 0 Reorder the terms: (-4 + 5c)(c + 6) = 0 Reorder the terms: (-4 + 5c)(6 + c) = 0 Multiply (-4 + 5c) * (6 + c) (-4(6 + c) + 5c * (6 + c)) = 0 ((6 * -4 + c * -4) + 5c * (6 + c)) = 0 ((-24 + -4c) + 5c * (6 + c)) = 0 (-24 + -4c + (6 * 5c + c * 5c)) = 0 (-24 + -4c + (30c + 5c2)) = 0 Combine like terms: -4c + 30c = 26c (-24 + 26c + 5c2) = 0 Solving -24 + 26c + 5c2 = 0 Solving for variable 'c'. Factor a trinomial. (-6 + -1c)(4 + -5c) = 0Subproblem 1
Set the factor '(-6 + -1c)' equal to zero and attempt to solve: Simplifying -6 + -1c = 0 Solving -6 + -1c = 0 Move all terms containing c to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1c = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1c = 0 + 6 -1c = 0 + 6 Combine like terms: 0 + 6 = 6 -1c = 6 Divide each side by '-1'. c = -6 Simplifying c = -6Subproblem 2
Set the factor '(4 + -5c)' equal to zero and attempt to solve: Simplifying 4 + -5c = 0 Solving 4 + -5c = 0 Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5c = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5c = 0 + -4 -5c = 0 + -4 Combine like terms: 0 + -4 = -4 -5c = -4 Divide each side by '-5'. c = 0.8 Simplifying c = 0.8Solution
c = {-6, 0.8}
| 0.7/20=n/100 | | 8-t/2=54 | | 5w=-1/3 | | 4t^2-25t+25=0 | | x+(x-5)+(x+20)=180 | | 2r^2-12r-146=-2 | | 14=.25(w-8) | | (-3x^2-7x+9)+(-5x^2+6x-4)=y | | -3x/4 | | 9x^9-72x^2= | | x^2=72+x | | 20(x)(x)(x)=1.99 | | 5z^2+10z-az-2a= | | (2/9)(-7) | | 2/5x+3 | | -2b+10=18 | | (-x+2x-4)+(-2x+4x-2)=y | | 16t^2+4t=600 | | m+1=m+2 | | -2y^2-200y+3200=0 | | 3r^2-6r=144 | | r/3+8=11 | | 4t^2+t-150=0 | | x=30-40 | | d=16(2.5) | | 2-x/3=-8 | | 2y^2-2y+32=0 | | 2085000000.00+5550000x=2500000000 | | 31-4x=0 | | y-(-2)=-1/2(x-1) | | d=12(2.5) | | 8+x/7=-3 |